PENGARUH PENGADOPSIAN INTERNET BANKING DAN DOMPET DIGITAL TERHADAP TRANSAKSI KEUANGAN PANDEMI COVID-19 - Hurian Kamela; Ryan Saputra Alam; Andrianto Prasetya Nugroho (Universitas Lancang Kuning, 2022)
The COVID-19 pandemic has directly changed people's habits to switch to online systems, including financial transactions. The most common are the use of internet banking and payments using digital wallets. The purpose of this study is to quantitatively analyze the use of internet banking and digital wallets in financial transactions based on Theory Of Planned Behavior (TPB). The method used is primary data (quantitative) by questionnaire as many as 62 people who use internet banking. This research was taken for 1 month, namely February 2021 (during COVID-19). The dependent variable used is Financial Transaction, while the other independent variables use 3 variables, namely Attitude, Norm and Behavior Control. The results of this study provide information that only attitude and norm have an effect on the financial effect. This provides evidence that the use of financial transactions via the internet is often done during the COVID-19 pandemic. This provides a new paradigm that financial transactions have begun to switch to using non-cash payments.